Social Housing in the Republic of Turkey - Kramer, Rafał (Acta Universitatis Lodziensis. Folia Oeconomica, 2021)
Social housing, as an element of the housing policy of every developed country, remains an important, though not fully explored, issue from both theoretical and practical perspectives. No uniform model of the functioning and financing of this part of the real estate sector has been introduced in Poland. In the paper, an attempt will be made to define social housing and to draw a line between the Polish terms of ‛budownictwo społeczne’ and ‛budownictwo socjalne,’ which, according to the author, cannot be treated as synonymous. The legal and institutional framework of the Turkish real estate market will be presented, with an emphasis on the specific characteristics of the Turkish model of social housing.